Multimodality imaging in cardiology: a statement on behalf of the Task Force on Multimodality Imaging of the European Association of Cardiovascular Imaging. (30th October 2018) - Fox, Kevin; Achenbach, Stephan; Bax, Jeroen; Cosyns, Bernard; Delgado, Victoria; Dweck, Marc R; Edvardsen, Thor; Flachskampf, Frank; Habib, Gilbert; Lancellotti, Patrizio; Muraru, Denisa; Neglia, Danilo; et al.
Abstract: